Mitigating psychological distress in healthcare workers as COVID-19 waves ensue: a repeated cross-sectional study from Jordan - Nour A. Obeidat; Yasmeen I. Dodin; Feras I. Hawari; Asma S. Albtoosh; Rasha M. Manasrah; Asem H. Mansour (BMC, 2022)
Abstract Background Jordan has experienced several COVID-19 waves in the past 2 years. Cross-sectional studies have been conducted to evaluate distress in healthcare practitioners (HCPs), but there is limited evidence with regards to the impact of continuing pandemic waves on levels of distress in HCPs. We previously studied psychological distress in HCPs during the start of the pandemic (period 1, when cases were infrequent and the country was in lockdown), and demonstrated that HCPs were experiencing considerable stress, despite the country reporting low caseloads at the time. In this study, we sought to utilize the same methodology to reexamine levels of distress as COVID-19 peaked in the country and HCPs began managing large numbers of COVID-19 cases (period 2). Methods A cross-sectional online survey utilizing a tool previously used during period 1 was completed by HCPs working in various settings. Demographic, professional and psychological factors such as distress, anxiety, depression, burnout, sleep issues, exhaustion, and fear were assessed; and coping strategies also were measured. Items in the tool were assessed for reliability and validity. A multivariable regression was used to identify factors that continued to impact distress during period 2. Results Samples in both periods (n = 937, n = 876, respectively) were relatively comparable in demographic characteristics, but in period 2, a greater proportion of nurses and healthcare practitioners reported working in general hospitals. During the pandemic peak (period 2), 49.0% of HCPs reported high levels of distress (compared to 32% in period 1); anxiety and depression scores were approximately 21% higher in period 2; and 50.6% reported fatigue (compared to 34.3% in period 1). Variables significantly associated with greater distress in period 2 included experiencing burnout, experiencing sleep disturbances, being fatigued, having fatalistic fears, and having fears related to workload. Conversely, being male, reporting satisfaction at work, and using positive coping practices were associated with a significantly lower odds of being in distress. Conclusions Between the two periods (early pandemic and first wave), COVID-19-related mental health continued to deteriorate among HCPs, highlighting the need to do more to support HCP front-liners facing COVID-19 surges.